Multi-Mode Absorption Spectroscopy (MUMAS) for multi-species trace gas sensing - Ewart, P (Wiley, 2019)
The technique of multimode absorption spectroscopy (MUMAS) is reviewed in the context of laser-based methods for gas sensing of multiple species. The principles and practical implementation of the method are outlined with examples of applications using lasers with outputs in spectral ranges from the visible to the mid-infrared, including interband cascade lasers (ICLs) and quantum cascade lasers (QCLs). The advantages and limitations of MUMAS are considered relative to other laser-based methods, and potential future developments and applications are suggested.